The role of the social supportin coping with the ischaemic pain - Kadłubowska, Monika; Kózka, Maria (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction: Social support is seen as a special way of giving help to people and groups who in order to cope with their problems have to mobilize their energy, potential and resources. It has also a great significance in fighting the ischaemic pain. Aim: The presentation of the role of the social support in coping with the pain among the patients suffering from the peripheral arterial disease (PAD). Material and methods: The study has been conducted on the group of 100 patients who were hospitalized due to the peripheral arterial disease in the District Hospital in Bielsko-Biała at the General and Vascular Surgery Ward as well as the patients who were treated in the General and Vascular Surgery Outpractice Clinic since December 2010 to January 2012. The methods used in the study included document analysis, a diagnostic survey with the usage of standardized investigation tools (Coping Strategies Questionnaire (CSQ), Social Support Scale by Krystyna Kmiecik-Baran), as well as a specially designed questionnaire. Results and conclusions: The predominant strategies used by the patients suffering from PAD were praying/hoping and claiming to cope with the situation. At the same time the strategy of reducing the pain was less frequent. Patients getting the instrumental support proved to use the strategy of reducing the pain infrequently. Thanks to the informative support the strategies of praying/hoping were less common. Patients who experienced evaluative support rarelyused the strategy of distracting, reassessing the feelings, claiming to cope, higher behavioural activity and controlling the pain. While getting the emotional support, patients used less frequently the strategy of praying/hoping, controlling the pain and the ability to reduce the pain, however, this kind of support favoured pessimistic thinking.